So French, so sweet : delectable cakes, tarts, crèmes and desserts - Gaté, Gabriel, 1955- (Hardie Grant Books, 2017)
"So French So Sweet is Gabriel Gat's love letter to patisserie, baking and sweet treats. An irresistible collection of French classics and Gabriel's most treasured sweet recipes, it brings together exquisite cakes and tarts, refreshing sorbets and fruity desserts, scrumptious ice creams, mousses and cremes and heavenly warm desserts. With a focus on fresh seasonal ingredients and home-style cooking, Gabriel shows just how simple it is to create delightful treats for everyone to enjoy"--Page [4] of cover.